Not all melanomas are created equal: a review and call for more research into nodular melanoma. (1st October 2021) - Dessinioti, C.; Geller, A.C.; Whiteman, D.C.; Garbe, C.; Grob, J.J.; Kelly, J.W.; Scolyer, R.A.; Rawson, R.V.; Lallas, A.; Pellacani, G.; Stratigos, A.J.
Summary: Among the histogenic subtypes of melanoma, nodular melanoma (NM) is the major contributor for thicker and fatal melanomas and it has been associated with melanoma‐specific death in thin tumours, highlighting an important subgroup of 'aggressive thin' melanomas. This review provides a synthesis of the distinct characteristics of NM, with respect to epidemiology and risk factors, clinical presentation, histopathology, molecular and dermoscopic aspects, and screening practices. The real challenges are to find better biomarkers of aggressiveness and to know whether the control of such aggressive melanomas can be influenced by targeted interventions such as early detection, drug interventions and preventive strategies.